RIGHT TO A DIGNIFIED LIFE IN THE PROCESS OF DEATH DURING THE EXERCISE OF THE RIGHT TO FREEDOM AND EUTHANASIA (Journal of Namibian Studies : History Politics Culture, 2023)
Human life implies more than just physical-biological existence; it implies the recognition and guarantee of the fulfillment of the fundamental right to life, which must coexist with other rights for its full expression to become effective. All States are under the obligation to ensure that the rights of individuals are made effective. Therefore, a dignified life requires a dignified death (dying process), since it is a fundamental right of all people. With the research carried out, it has been found that the non-regulation of euthanasia as a medical practice that puts an end to the suffering of the terminally ill causes the constant violation of other rights since the recognition of a dignified life is conceived to be fulfilled during the entire stage of life of people. In the present study, two research methods were used, such as the comparative and the legal dogmatic. With the application of these methods, valuable information has been obtained regarding euthanasia, which has made it possible to demonstrate the need and importance of regulating it within the Ecuadorian legal system. The Ecuadorian State must establish the necessary guarantees and mechanisms that make effective the enjoyment of people's rights, so this research aims to establish the need to create a legal norm that regulates the practice of euthanasia within the Ecuadorian legal system as a rule that guarantees the right to a dignified life in the process of death of patients or terminally ill patients.